2011
DOI: 10.1021/jp208576v
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics, Kinetics, and Modeling Investigation on the Dehydrogenation of CeAl4-Doped NaAlH4 Hydrogen Storage Material

Abstract: The CeAl4-doped NaAlH4 has been synthesized by mechanical milling NaH/Al mixture with 4 mol % CeAl4 as catalyst under hydrogen pressure of 3 MPa. The hydrogen desorption thermodynamics and kinetics of as-synthesized NaAlH4 were systematically investigated. The enthalpies for the first and second dehydrogenation steps of CeAl4-doped NaAlH4 system are estimated to be 40.56 ± 1.62 and 51.48 ± 1.92 kJ/mol H2, respectively. By regulating the desorption temperatures, the two dehydrogenation steps were studied separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Though the cost of synthesis and preparation time of colloid-Ti was too high, the method was no longer considered for the doping. Fan et al [33] investigated energy and hydrogen desorption thermodynamics of CeAl 4 -doped NaAlH 4 and found the separation level for second-step desorption to be 0.096 MPa at 120 • C. More recently synthesized Ti 2 and TiN catalysts for the synthesis of sodium-alanate through mechanical milling reported remarkably mild recharging conditions of 90 • C at 4 MPa H 2 pressure. The results were similar for high-pressure hydrogen (50 bar 2 ), suggesting good reversibility of TiN-doped NaAlH 4 [34].…”
Section: Sodium Alanate Systemmentioning
confidence: 99%
“…Though the cost of synthesis and preparation time of colloid-Ti was too high, the method was no longer considered for the doping. Fan et al [33] investigated energy and hydrogen desorption thermodynamics of CeAl 4 -doped NaAlH 4 and found the separation level for second-step desorption to be 0.096 MPa at 120 • C. More recently synthesized Ti 2 and TiN catalysts for the synthesis of sodium-alanate through mechanical milling reported remarkably mild recharging conditions of 90 • C at 4 MPa H 2 pressure. The results were similar for high-pressure hydrogen (50 bar 2 ), suggesting good reversibility of TiN-doped NaAlH 4 [34].…”
Section: Sodium Alanate Systemmentioning
confidence: 99%
“…Apart from Ti-containing compounds, other transitionmetal, MOFs, rare-earth-metal-based compounds have also been explored and investigated as dopants, which were proved to be able to enhance hydrogen storage properties of alanates [193,[235][236][237][238][239][240][241][242][243][244]. Bogdanović et al [235][236][237] revealed that CeCl 3 and ScCl 3 additives could remarkably promote the hydrogen desorption kinetics of NaAlH 4 and LiAlH 4 .…”
Section: Adding Dopantsmentioning
confidence: 99%
“…Hydrogen storage properties of additive-doped lightweight metal alanates Ti x specie. Fan et al[238,239] investigated the enhanced hydriding-dehydriding properties of Ce-Al species-doped NaAlH 4 . Assynthesized CeAl 2 -doped NaAlH 4 released around 70% of the hydrogen capacity in the first hydrogen evolution step at 160°C within 6 min, and could be hydrogenated under 12 MPa hydrogen pressure at 120°C in 20 min, with a hydrogen capacity of 4.9 wt%.…”
mentioning
confidence: 99%
“…Similar to a TiCl 3 doped NaAlH 4 system, a CeCl 3 doped system exhibited the formation of Ce-Al species, which are considered as catalytically active for the decomposition of NaAlH 4 [205]. Thus, CeAl 2 and CeAl 4 alloys were directly mixed to NaAlH 4 and were found to be quite effective in reducing the activation energy of both steps, which were found in the range of 72-90 and 93-104 kJ/mol H 2 for first and second step decomposition [206,207]. Similar to NaAlH 4 system, several catalysts were developed for solving the kinetic problem of LiAlH 4 decomposition, which included Ti based halides [208][209][210][211], other metal halides [212][213][214][215][216][217][218], nano-sized oxides [219][220][221], carbon [222][223][224], etc.…”
Section: Catalysts For Alanatesmentioning
confidence: 99%